An Overview of Attendance and Participation in Online Class During the COVID Pandemic: A Case Study - Qutishat, Duha; Obeidallah, Randa; Qawasmeh, Yasser (International Journal of Interactive Mobile Technologies (iJIM), 2022)
COVID-19 pandemic has transformed the traditional education in all levels to be shifted to online classrooms. Monitoring student’s attendance and interaction during live online classes is a challenge for educators. During the lockdown, many factors influenced the participation and attendance to online class, which we will highlight them in this research. This research investigated the participation of students registered in course Introduction to Web Programming Lab at Hashemite University. Students’ participation was measured based on attendance, class interaction, assignment delivery, and utilization of e-learning platforms. Students’ course learning outcomes (CLOs) were investigated and evaluated using a survey. Number of students who were evaluated during autumn (1st semester) and spring (2nd semester) semesters 2020/2021 is 212 students. Findings indicated that online education was successfully implemented, and material content were understood by students. Further analysis showed that the interaction of students during the meeting class is considered low.